Um sistema de gerenciamento integrado e automatizado de serviços e computadores de redes locais - Kreutz, Diego Luis (2005)
The management of computer networks is an area that demands competence, creativeness, imagination, action, observation, autonomy and a lot of work. Even today it is still an area with a lack of tools and professionals qualified to the management of the most diverse administrative domains. In this context, this work describes the project and development of an integrated, dynamic and automated system that is able to simplify and reduce the time required by for many daily tasks of network administrators. The proposed system can also be used as a way of integrationg existing management tools, making use of their resources and functionalities. The results validate and show the appliance of the system. A prototype of the system was developed, that could already be applied to automate many administrative tasks of computer networks.